2020
DOI: 10.3390/jcm9103360
|View full text |Cite
|
Sign up to set email alerts
|

Belching in Gastroesophageal Reflux Disease: Literature Review

Abstract: Belching is a common phenomenon. However, it becomes bothersome if excessive. Impedance–pH monitoring can classify the belching into two types: gastric belching and supragastric belching (SGB). The former is a physiological mechanism to vent swallowed air from the stomach, whereas the latter is a behavioral disorder. Gastroesophageal reflux disease (GERD) is the most relevant condition in both types of belching. Recent findings have raised awareness that excessive SGB possibly sheds light on the pathogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 81 publications
1
6
0
8
Order By: Relevance
“…La importancia en la práctica clínica radica en identificar los eructos supragástricos, ya que (como desarrollaremos más adelante) son los que constituyen una potencial causa de refractariedad al tratamiento y presentan un enfoque terapéutico diferente. 17,18 del gas en el esófago, así como su eventual relación con el reflujo y los síntomas. 23 • Eructos gástricos Con cada deglución, ingerimos un volumen variable de aire que es transportado al estómago.…”
Section: Eructosunclassified
See 2 more Smart Citations
“…La importancia en la práctica clínica radica en identificar los eructos supragástricos, ya que (como desarrollaremos más adelante) son los que constituyen una potencial causa de refractariedad al tratamiento y presentan un enfoque terapéutico diferente. 17,18 del gas en el esófago, así como su eventual relación con el reflujo y los síntomas. 23 • Eructos gástricos Con cada deglución, ingerimos un volumen variable de aire que es transportado al estómago.…”
Section: Eructosunclassified
“…Si bien los monitoreos de Estos pacientes pueden acudir a la consulta por el eructo en sí (fenómeno audible), mientras que en otros puede manifestarse únicamente con síntomas típicos de reflujo. 18 • Epidemiología…”
Section: Eructosunclassified
See 1 more Smart Citation
“…However, the prevalence of belching in GERD patients varies widely, 4.1-75.6%. 5 A Dutch study revealed that the incidence of SGB was significantly higher in GERD patients with severe belching compared to GERD patients with mild to moderate belching, therefore, they suggested that SGB, and not gastric belching influence the reflux symptoms in patients with GERD. 6 A recent cross-cultural study reported that the prevalence of SGB and its effect on GERD symptoms is significantly lower in Japanese patients compared to British patients.…”
mentioning
confidence: 98%
“…Thus far, BD in the Asian population is still not clearly elucidated, there are few studies on BD and GERD patients with belching that have been conducted on an Asian population and especially in Korean patients. A recent review reported that the prevalence of belching in the general population varies from 6.7-28.8%, 5 however most of the studies were conducted in the Western nations.…”
mentioning
confidence: 99%